1984
DOI: 10.1126/science.224.4649.621
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of a Larval Herring Population by Jellyfish Predator

Abstract: The scyphomedusa Aurelia aurita consumes large amounts of yolk-sac herring larvae in Kiel Fjord. The decline of the larval herring population in late spring coincides with a major population growth of the jellyfish. The size of the larval herring population seems to be more significantly affected by the size of the predator stock than by the size of the parental herring stock.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
92
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(93 citation statements)
references
References 3 publications
1
92
0
Order By: Relevance
“…However, understanding of the ecological role of gelatinous zooplankton in Namibian waters is limited at present. For example, the impact of the group on fish recruitment (particularly as a result of predation on eggs and larvae) could be considerable (Möller 1984.…”
Section: What Is the Potential Strength Of Competitive Interactions Bmentioning
confidence: 99%
“…However, understanding of the ecological role of gelatinous zooplankton in Namibian waters is limited at present. For example, the impact of the group on fish recruitment (particularly as a result of predation on eggs and larvae) could be considerable (Möller 1984.…”
Section: What Is the Potential Strength Of Competitive Interactions Bmentioning
confidence: 99%
“…Moon jellyfish are considered to be important predators of fish larvae as well as other invertebrate plankton (Bailey & Batty 1984, Sullivan et al 1994. Möller (1984) observed 68 Atlantic herring Clupea harengus (Linnaeus 1758) larvae were eaten by a single moon jellyfish (42 mm in bell diameter: BD) in Kiel Fjord. Recent laboratory experiments reported that more than 110 red sea bream Pagrus major (Temminck et Schlegel 1844) larvae were preyed on by a moon jellyfish (66-80 mm BD) during a short-term satiation experiment (Nakayama et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Larval mortality can affect larval supply and, subsequently, recruitment (Milicich et al, 1992). There are many sources of larval mortality including starvation (e.g., Cushing, 1975Cushing, , 1990, predation (e.g., Moller, 1984;McGurk, 1986) and expatriation (e.g., Sponaugle and Pinkard, 2004). Starvation can be a major source of mortality in fish larvae (Leggett and Deblois, 1994).…”
Section: The Recruitment Of Lutjanus Carponotatus To One Tree Islandmentioning
confidence: 99%
“…As large numbers of larvae are produced, small changes in the pre-settlement mortality rate can greatly affect the strength of recruitment events (Cowen et al, 2000;Houde, 2008). The pre-settlement mortality rate of fish larvae can depend on multiple factors including the availability of food (e.g., Cushing, 1975Cushing, , 1990, the abundance of predators (e.g., Moller, 1984;McGurk, 1986) and favorable or unfavorable oceanography (e.g., Sponaugle and Pinkard, 2004;Sponaugle et al, 2005), and this complexity can make it difficult to identify causes of variability in recruitment (Leggett and Deblois, 1994;Houde, 2008).…”
Section: Introductionmentioning
confidence: 99%